Immersion in Cold-Water Evaluation (ICE) and Self-reported Cold Intolerance are Reliable but Unrelated Measures - Traynor, Robyn (Springer-Verlag, 2008)
Intolerance to the cold is common following peripheral nerve injury and surgery of the upper extremity. Despite its prevalence, the exact pathophysiology and natural history of this condition are not well understood. Subjective, self-report questionnaires have been created and validated as reliable measures of post-traumatic cold intolerance. The difficulty currently lies in assigning an objective measure to this predominantly subjective phenomenon. The present study evaluated the test–retest reliability of a proposed objective measure of cold intolerance, the Immersion in Cold-water Evaluation (ICE), and its correlation with subjective measures in healthy control subjects. Two age groups were also compared to investigate the effect of age on cold intolerance and temperature recovery. On two separate testing days, subjects completed three health-related questionnaires and submersed their dominant hands in cold water. The temperature of their second and fifth digits was monitored during recovery. Both the objective cold-provocation testing and the subjective self-report questionnaires were highly reliable albeit not significantly correlated. No significant temperature recovery trend was noted between the age groups. Post-traumatic cold intolerance is postulated to have both a vascular and neural etiology among other contributing causes. The protocol studied here was centered predominantly on the former etiology, examining peripheral blood flow and associated temperature recovery. This study established ICE as a reliable means to objectively measure cold response, supplementing information provided by previously validated self-report methods.